Exploring Mathematical Concepts in Buna Woven Fabric Motifs of the Amanuban Community and Their Integration into Mathematics Education - Daniel, Farida; Turmudi, Turmudi; Juandi, Dadang; Kusnandi, Kusnandi (Newinera Publisher, 2025)
This study explores the mathematical concepts embedded in the woven motifs of Buna, specifically Tais Kaimnutu and Buna Panbuat, from the Amanuban community, and their potential integration into mathematics education. Using a qualitative ethnographic approach, the researchers conducted six months of observations, interviews with indigenous weavers and cultural experts, and documentation of woven patterns. The study reveals that Buna woven motifs embody rich mathematical concepts such as symmetry, geometric transformations, fractals, and group theory, while also reflecting deep cultural values, identity, and spirituality. These motifs serve as intuitive artistic and cosmological expressions, with mathematical interpretations offering a new form of cultural appreciation that respects local contexts. Educationally, these motifs support learning across all levels: introducing symmetry and spatial visualization in elementary school; deepening understanding of transformations and congruence in middle school; exploring fractals and algebraic structures in high school; and fostering culturally responsive teaching in higher education through ethnomathematics integrated with mathematical modeling and topology. Beyond pedagogy, the study emphasizes the importance of integrating indigenous knowledge into formal curricula to strengthen cultural identity, community involvement, and empowerment. It highlights ethnomathematics as a transformative bridge linking academic research, cultural preservation, and community development. Future research should explore participatory curriculum design and community perspectives on the mathematical interpretation of indigenous crafts to enhance educational and cultural sustainability.